2016
DOI: 10.1039/c5tc02993g
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency noise and photo-enhanced field emission from ultrathin PbBi2Se4 nanosheets

Abstract: PbBi2Se4 nanosheets demonstrate high performance and extremely stable photosensitive field emission with low frequency noise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…[38] Some of the TIs, Bi 2 Se 3 , and PbBi 2 Se 4 have been studied for their FE behavior. [39][40][41] These planar emitters have shown promising characteristics, which are attributed to the robust conducting surface states. Recently our group has reported FE characteristics of hydrothermally synthesized Sb 2 Te 3 micron-sized hexagonal platelets.…”
Section: Introductionmentioning
confidence: 99%
“…[38] Some of the TIs, Bi 2 Se 3 , and PbBi 2 Se 4 have been studied for their FE behavior. [39][40][41] These planar emitters have shown promising characteristics, which are attributed to the robust conducting surface states. Recently our group has reported FE characteristics of hydrothermally synthesized Sb 2 Te 3 micron-sized hexagonal platelets.…”
Section: Introductionmentioning
confidence: 99%
“…From the temperature‐dependent electrical conductivity and Seebeck coefficient analysis, it is revealed that PbBi 2 Se 4 has high mobility of charge carriers at room temperature. Recently, Suryawanshi et al reported the photofield emission behavior and spectral analysis of few layered PbBi 2 Se 4 nano‐sheets emitter under visible light illumination. The photo field behavior was envisaged by reduction in turn‐on field and delivery of higher emission current density at relatively lower applied field, which is attributed to photosensitive nature of PbBi 2 Se 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Such a process makes actively controlled ultra-fast electron emission possible [18][19][20][21], thus forming a series of applications, such as the state-of-the-art time-resolved electron microscopy and spectroscopy that can access temporal dynamics on a solid surface with high spatial resolution [22][23][24]. In addition, more importantly, this laser-triggered optical field has been demonstrated to assist in the field electron emission process and improve the performance from a specific emitter by taking advantage of the synergy with the fixed electrostatic field [25][26][27][28]. However, the corresponding in situ analysis is insufficient to reveal the essence of such a multi-fields-driven electron emission, although some preliminary results about polarization dependence as well as emitted electron spectrum have been reported on a carbon nanotip sample [29].…”
Section: Introductionmentioning
confidence: 99%